GASIFIKASI ARANG KAYU UNTUK PEMBANGKITAN TENAGA LISTRIK - Hartoyo Hartoyo; Tjutju Nurhayati Syachri (Jurnal Penelitian Hasil Hutan, 1986)
An  experiment  on  charcoal  gasification   for  power  generation   was  conducted    on  a pilot   scale  of  7.5 KVA.   This experiment  used  50  kg  mixed  charcoal  species  having  moisture  content   of  6.9  %, ash content   of 2.5 %, volatile  matter  of  22.4  % and calorific  value of 6733  cal/g.The  product gas was run  through  gas purifier,  jet  condenser,  cyclone,  gas cooler and filter.  The gas was composed   of carbon  monoxide  (26  to  31%),   carbon  dioxide  (3  to  15%), methane  (0 to 1%) with  calorific  values ranging from  2600  to 4100  cal/g.The produce  gas which  was assumed   to  have  been purified   of  tar and  water  vapour  was fed  into  a power  generator.The  electric  power  generated   ranged  from   200   to  234  Volts  at around  2.08  A  and  a revolution   of  from   1822  to 2110 RPM. It  turned  out  that  these gases still  contained   tar and  water  vapour  which  was observed  at the engine,  an indication that  the  gas purifier   did  not  function  weel.  This  is evidenced   by  the fluctuation  of  the gas flow  rate  (from  9.8  to  1277 Nm3/hour).The  efficiency   of  charcoal  conversion   to  electric  and  heat  energy   was  11. 7% and  60% respectively   for  a load of 1.8  KW  and  7 hours  of  operation,   and  13,9  % and  50.5   % respectively   for  a load  of  2.8  KW  and  7 hours  of  operation.